The Association of VDAC with Cell Viability of PC12 Model of Huntington’s Disease - Karachitos, Andonis; Grobys, Daria; Kulczyńska, Klaudia; Sobusiak, Adrian; Kmita, Hanna (Frontiers in Oncology, 2016)
It is becoming increasingly apparent that mitochondria dysfunction plays an important role in pathogenesis of Huntington’s disease (HD) but the underlying mechanism is still elusive. Thus, there is a still need for further studies concerning the upstream events in the mitochondria dysfunction that could contribute to cell death observed in HD. Taking into account the fundamental role of the voltage-dependent anion-selective channel (VDAC) in mitochondria functioning it is reasonable to consider the channel as a crucial element in HD etiology. Therefore, we applied inducible PC12 cell model of HD to determine the relationship between the effect of expression of wild type and mutant huntingtin (Htt and mHtt, respectively) on cell survival and mitochondria functioning in intact cells under conditions of undergoing cell divisions. Because after 48h of Htt and mHtt expression differences in mitochondria functioning co-occurred with differences in the cell viability we decided to estimate the effect of Htt and mHtt expression lasted for 48h on VDAC functioning. Therefore we isolated VDAC from the cells and tested the preparations by black lipid membrane (BLM) system. We observed that the expression of mHtt, but not Htt, resulted in changes of the open state conductance and voltage-dependence when compared to control cells cultured in the absence of the expression. Importantly, for all the VDAC preparations we observed a dominant quantitative content of VDAC1 and the quantitative relationships between VDAC isoforms were not changed by Htt and mHtt expression. Thus, Htt and mHtt-mediated functional changes of VDAC, being predominantly VDAC1, which occur shortly after these protein appearance in cells may result in differences concerning mitochondria functioning and viability of cells expressing Htt and mHtt. The assumption is important for better understanding of cytotoxicity as well as cytoprotection mechanisms of potential clinical application.